Analisis Prediksi Harga Saham Sinar Mas Group - Versiandika Yudha Pratama; Wilda Yulia Rusyida (Jurnal Pasar Modal dan Bisnis, 2020)
This study aims to determine the Sinar Mas Group's daily stock price predictions on the issue of inheritance claims using the ARIMA and SARIMA methods. The data used in this study are secondary data in the form of historical daily stock price data from January 1st, 2019 to July 24th, 2020. The results of this study showed that BSIM stock predictions obtained with SARIMA (1,0,1) (0,1,1), the stock price trend was down but not too large. INKP with ARIMA (2,1,3); MCOR with SARIMA (1,0,0) (0,1,1); SMAR with ARIMA (0,1,3); and TKIM with SARIMA (1,0,1) (1,1,1) showed a declining stock price trend. Meanwhile, the prediction of SMMA obtained with ARIMA (3,1,2) shows an upward trend in stock prices. Technically, to take advantage of the short-term momentum, buy on weakness for SMMA which has an upward trend, while for BSIM, INKP, MCOR, SMAR and TKIM whose trend is declining can take steps to sell it.